China's new nationalism : pride, politics, and diplomacy - Gries, Peter Hays, 1967- (Philip E. Lilienthal Books (Paperback), 2004)
At a time when the direction of China's foreign and domestic policies have profound ramifications worldwide, Gries offers a rare, in-depth look at the nature of China's new nationalism particularly as it involves Sino-American and Sino-Japanese relations.